The relationship between gut microbiota and weight gain in humans. (January 2012) - Angelakis, Emmanouil; Armougom, Fabrice; Million, Matthieu; Raoult, Didier
The human gut microbiota is a metabolic organ that is determined by a dynamic process of selection and competition. Age, dietary habits and geographical origin of people have an important impact on the intestinal microbiota. The role of the microbiota is still largely unknown, but the bacteria of the gut flora do contribute enzymes that are absent in humans and play an essential role in the catabolism of dietary fibers. Germ-free mice provide a complementary approach for characterizing the properties of the human gut microbiota. Recently, microbial changes in the human gut were proposed to be one of the possible causes of obesity. This review summarizes the latest research on the association between microbial ecology and host weight.